Contextualizing decision-making in international business through scenario-based method - Ricard, Antonin; Reynaud, Emmanuelle; Bertrand, Daisy; Shahid, Subhan (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
The objective of this study is to introduce, develop, and validate a scenario-based method to study the influence of context in international business decision-making. Scenario-based methods use real-life situations to collect data or measure context-sensitive constructs. This study includes the development of a scenario and five behavioral answers using a five-step process and rigorous data collection. Based on multiple interviews and a final sample of decision-makers from 149 French small and medium-sized enterprises (SMEs), the measurement tool’s internal and external validity meets the criteria of scale development. The tool enables the study of internationalization decision-making from new perspectives—for instance, through more rigorous contextual research or exploration of sensitive topics such as cognitive factors, motives, and behaviors in international business research.